Volumetric Arc Therapy versus Conventional Image Guided Radiotherapy in Head and Neck Cancer Patients - Wang, Kevin Johan (UiT Norges arktiske universitet, 2020)
Research goal: To compare the survival outcomes, and patterns of loco-regional and metastatic recurrence of patients treated with primary radiotherapy for H&N cancer in different time periods where either conventional IGRT, IMRT or VMAT were available. Introduction: Conformal techniques are attractive for treating H&N cancer as fields may be shaped to spare critical organs. As a result, H&N cancer emerged as one of the first standard indications of IMRT/VMAT when these techniques became available. However, there exists few studies which evaluates patterns of recurrences. Methods: 292 patients receiving definitive radiotherapy for H&N cancer at the Department of Oncology at UNN Tromso between 2005-2015 were included. Patients were grouped according to available treatment technique (IGRT, IMRT and VMAT). Overall, disease-specific, loco-regional failure free and metastasis free survival were compared. Results: Our study suggests a slightly longer loco-regional recurrence free survival (p=0,066) in the period IMRT/VMAT were available, compared to when only 3D-IGRT was available. However, increased understanding of the tumor biology and the introduction of advanced diagnostic tools during the study period, precludes a definitive conclusion. Overall survival.